The Problems of Writing Arabic Letters for Islamic Junior High School Students - Alhumaira, Adinda Fuadilah; Lubis, Lahmuddin (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2023)
This study aims: 1) To find out the problems experienced by class VII students in learning to write Arabic script, and 2) To find out the Arabic teacher's solutions in solving the problems of learning to write Arabic script for class VII students of MTs Aek Nabara. The subjects of this research were class VII students of MTs Aek Nabara. This research is qualitative research with a case study approach. The data collection method used in this research is observation, interview, and documentation. Data analysis was carried out through data reduction, data presentation, and drawing conclusions. The results of the study showed that class VII students at MTs Aek Nabara faced problems learning to write Arabic scripts. The problems faced based on the results of the interviews are 1) Not knowing Qo'idah Imla'iyah. 2) The pattern of the Arabic sentence is different from the Indonesian sentence pattern. 3) Lack of recognition of the shape or writing of Arabic letters and others. The solutions that can be done are 1) Using a variety of methods in teaching, including deliberations, so that students don't feel bored. 2) Collect data about students who have learning difficulties. 3) Pay special attention to students who have learning difficulties by frequently asking questions during the teaching and learning process. Thus it can be seen that Arabic writing is a subject that must receive intensive assistance, especially in learning methodology.